Implementation of Corporate Legal Liability for Work Accidents in the Perspective of Occupational Safety and Health (K3): A Case Study on PT Hari Sawit Jaya Negeri Lama - Andina Resty; Dea Fadila; Farida Hanum fajrianti; Annisa Octavia; Khairul Ali Harahap (Jurnal Cendikia ISNU SU, 2024)
Work accidents are one of the important issues in industrial relations because they are directly related to the fulfillment of workers' rights to occupational safety and health protection (K3). In the oil palm plantation sector, which has a high level of occupational risk, companies have a legal obligation to create a safe working environment and be responsible for workers in the event of a work accident. The problems in this study focus on the implementation of the company's legal obligations in the implementation of K3 and the form of legal liability of PT Hari Sawit Jaya Negeri Lama for work accidents that occur in the company's environment. This study aims to analyze the implementation of company obligations based on the provisions of Law Number 13 of 2003 concerning Manpower and Law Number 1 of 1970 concerning Occupational Safety and to find out the form of legal protection provided to workers who are victims of work accidents. The research method used is empirical legal research with a statutory approach and a case approach. The research data was obtained through field research in the form of interviews with workers and former workers of PT Hari Sawit Jaya Negeri Lama, then analyzed qualitatively by connecting field facts and applicable legal provisions. The results of the study show that PT Hari Sawit Jaya Negeri Lama has carried out its legal responsibilities through the provision of occupational safety facilities, K3 training, the implementation of safety procedures, and the provision of protection through BPJS Ketenagakerjaan. However, the company's responsibility is not only limited to providing guarantees after an accident occurs, but also includes efforts to prevent and improve the work safety system on an ongoing basis. In conclusion, PT Hari Sawit Jaya Negeri Lama has fulfilled most of its legal obligations in worker protection, although optimizing the implementation of K3 is still needed to minimize the risk of work accidents.